2021
DOI: 10.3390/ma14020432
|View full text |Cite
|
Sign up to set email alerts
|

Study of Concrete Strength and Pore Structure Model Based on Grey Relation Entropy

Abstract: The Grey Relation Entropy (GRE) theory is used to analyze the sensitive pore size that affects the compressive strength of concrete. The relationship between the strength and pore structure is revised based on the sensitivity coefficient. The revised model is used to calculate the compressive strength of concrete. In order to verify the validity of the proposed model, the calculated results are compared with experimental ones, showing satisfactory agreement with a larger correlation than existing methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The average value of the grey correlation coefficients is taken as the correlation degree. The closer the value is to 1, the better the correlation degree is [23,25,26].…”
Section: Grey Correlation Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average value of the grey correlation coefficients is taken as the correlation degree. The closer the value is to 1, the better the correlation degree is [23,25,26].…”
Section: Grey Correlation Analysis Methodsmentioning
confidence: 99%
“…To some extent, porosity, pore diameter, and pore size distribution have a vital influence on the macro performance of the high water grouting material, and thus, the grey correlation theory was applied to evaluate the correlation between pore structure and compressive strength [23,25,26]. Furthermore, the relevant equation was established.…”
Section: The Relationship Between Pore Structure and Compressive Strengthmentioning
confidence: 99%
“…Zhao et al (Zhao et al, 2014) established an extended the "Bhattacharjee" model (Rakesh and BHATTACHARJEE, 2003) considering porosity, average pore size, and hydration degree, which can clearly describe the relationship between the pore structure characteristics and strength of cement mortar. Based on this model, Zhang et al (Zhang et al, 2021) analyzed the influence of pore size distribution on strength, obtained the sensitive pore size that affects the compressive strength of concrete, and corrected the existing model according to the sensitivity coefficient. The results indicated that this model possessed a greater correlation with the calculation results than the existing model.…”
Section: Influence Mechanism Of Pore Distribution On Mechanical Stren...mentioning
confidence: 99%
“…α is the degree of hydration, and d m is the average pore size Bu and TIAN (2016) σ σ 0 exp(aP + bL + cr 2 ′ + dd 0 ) L is the total pore volume parameter, r 2 ′ is the pore shape parameter, and d 0 is the critical pore diameter. The aforementioned parameters can be obtained from the MIP curve Zhang et al (2021) σ αK 2 B s √ C(1 − P)/ d m C is the cement content parameter, K 2 is the experimental constant, B s is the sensitive pore size distribution coefficient, and α is the coefficient…”
Section: References Model Remarkmentioning
confidence: 99%
“…e closer the two compared sequences are, the larger the correlation degree is, and the inverse also holds [21]. In this paper, Dunn's correlation degree model is used, and the expression [22] is…”
Section: Grey Relational Analysis Evaluation Modelmentioning
confidence: 99%